Estimation of Avalanche Hazard in the Settlement of Magurka Using ELBA+ Model - Bartík, Martin; Hríbik, Matúš; Hanzelová, Miriam; Škvarenina, Jaroslav (GeoScience Engineering, 2013)
In our study we focused on advanced software applications to allow simulation of an avalanche. We used the model ELBA+, by which we tried to assess the vulnerability of mountain environments around the old mining settlement called Magurka (1036 m a.s.l.), which lies below the main ridge of Low Tatras at the end of Ľupčianská valley. The avalanche in the Ďurková valley released on 14th March 1970 went down in history because it is still one of the largest avalanches recorded in Slovakia. Using archived data of the Avalanche Prevention Centre in Jasná, we tried its most faithful reconstruction. Then we tried to simulate an avalanche in the Viedenka valley using the same amount of snow in the release zone as it was supposed to be in 1970. Because a part of the Magurka settlement is situated at the mouth of this valley, which has more direct and shorter terrain than the valley of Ďurková, we examined the possibility of intervention by the avalanche.